Library usage by DDUH students and staff (Journal of EAHIL, 2025)
Aim: To explore the accessibility, functionality, and effectiveness of Dublin Dental University Hospital (DDUH) library services for students and staff.Methods: A validated survey assessed satisfaction with library hours, study spaces, resources, online databases, and preferred study environments among students (dental nursing, technology, hygiene, science) and staff.Results: Of 217 respondents (86.2% students, mostly dental science), 68.7% were satisfied with library hours, though undergraduates favored extended and weekend access (p=0.015). Online database difficulties affected 32.3%, highest among dental technology students (57.9%, p=0.025). Study spaces were most valued; librarian services least. Most requested additional quiet, group, and lounge areas. Despite alternatives, 68.7% considered DDUH Library optimal.Conclusions: Extended hours, improved study spaces, digital training, and promoting librarian services are essential to enhance accessibility and meet evolving needs.Keywords (MeSH) terms: Libraries; Students, Dental; Education,